2022
DOI: 10.7759/cureus.29304
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Monkeypox: A Global Health Threat

Abstract: Monkeypox (MPX) is a zoonotic disease caused by the monkeypox virus (MPXV) belonging to the Orthopoxvirus genus. It results in a smallpox-like disease in humans. Recently, MPX has been declared a public health emergency of international concern. The disease is characterized by fever, muscle ache, malaise, and pustules. The presence of characteristic significant lymphadenopathy helps it to be differentiated from other similar illnesses. Early detection of cases and effective contact tracing is necessary for bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Study with phytochemicals is missing in literature; however, our team has published several reviews and editorial paper on monkeypox outbreak with promising insight into future perspectives. [29][30][31][32][33][34] Our present study cannot be compared with previous studies as till date no in silico docking of MPXV with phytochemicals is reported.…”
Section: Molecular Docking Analysismentioning
confidence: 73%
“…Study with phytochemicals is missing in literature; however, our team has published several reviews and editorial paper on monkeypox outbreak with promising insight into future perspectives. [29][30][31][32][33][34] Our present study cannot be compared with previous studies as till date no in silico docking of MPXV with phytochemicals is reported.…”
Section: Molecular Docking Analysismentioning
confidence: 73%
“…In contrast, fear of international flights suspension was reported as the less worrying factor among the study population and, the major worries during the COVID-19 were from the high mortality rates and morbidities associated with the disease [17,21]. Although there is not a specific vaccine that protects against MPXV, many orhtopoxvirus vaccines were found to cross-protect against MPXV by the antigenic similarity [22,23]. Smallpox vaccines have great efficacy in prevention of MPX infection with clinical effectiveness of about 85% [24].…”
Section: Discussionmentioning
confidence: 98%
“…According to CDC, two smallpox vaccines (ACAM2000 AND JYNNEOS) are approved to be used in protection against both smallpox and MPX in the US [25]. Monkeypox vaccination can be given as either preexposure or post-exposure immunization [22,24,25]. While pre-exposure vaccination can reduce the risk of catching the infection, post-exposure vaccination within 4-14 days can ameliorate the symptoms of the disease and help the rapid recovery [24].…”
Section: Discussionmentioning
confidence: 99%
“…Most mpox infections are mild and resolve without specific therapies within 2-4 weeks following infection 11 . Primary treatment upon hospitalization has consisted of supportive management of mucosal lesion pain, proctitis, and mitigation of secondary infections of the skin 18,19 . Considerations for general pain control include overthe-counter medications (OTC) such as acetaminophen and non-steroidal anti-inflammatory drugs (NSAIDs).…”
Section: Managementmentioning
confidence: 99%
“…In August 2022, an Emergency Use Authorization issued by FDA approved the vaccination for mpox 28 . However, there have been reports of injection site pain, redness, and swelling 18 . Unlike ACAM2000, extensive trials regarding adverse events have yet to be conducted 27 , which is another area that requires additional research.…”
Section: Vaccinationmentioning
confidence: 99%